Pertanggungjawaban Pelaku Usaha dalam Peredaran Iphone Paraller Import (Black Market) Ditinjau dari Undang Undang Nomor 8 Tahun 1999 - Gilbert Parsaulian Hutapea; I Nyoman Bagiastra (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The rapid development of communication technology has spurred public demand for smartphones, particularly iPhones, seen as a symbol of prestige and advanced technology. This high demand has been exploited by unscrupulous business actors who distribute parallel import (black market) iPhones that are not officially registered, posing risks to consumers. This study examines the legal protection procedures for consumers, the legal standing of consumers in black market iPhone transactions, and the liability of business actors under Law Number 8 of 1999 concerning Consumer Protection (UUPK). Using a normative legal research method, the study employs statutory and conceptual approaches, analyzing primary, secondary, and tertiary sources. The findings indicate that consumer protection can be achieved through preventive measures such as public education and information transparency, and repressive measures via dispute resolution mechanisms, both in court and through the Consumer Dispute Settlement Agency (BPSK). Consumers' legal rights are acknowledged, though they remain vulnerable due to the purchase of illegal goods. Business actors may be held liable for product liability, including the obligation to provide accurate information and face sanctions. In conclusion, consumer protection in black market iPhone transactions remains insufficient, and stronger enforcement is necessary.